Impedance analysis and dielectric response of anatase TiO2 nanoparticles codoped with Mn and Co ions. (28th November 2017) - Kumar, Anand; Kashyap, Manish K; Sabharwal, Namita; Kumar, Sarvesh; Kumar, Ashok; Kumar, Parmod; Asokan, K
Abstract: In order to elucidate the effect of transition metal (TM) doping, the impedance and dielectric responses of Co and/or Mn-doped TiO2 nanocrystalline powder samples with 3% doping concentration synthesized via sol gel technique, have been analyzed. X-ray diffraction (XRD) analysis confirms the formation of tetragonal TiO2 anatase phase for all studied samples without any extra impurity phase peaks. The variation in the grain size measured from field emission scanning electron microscope (FESEM) measurements for all the samples are in accordance with the change in crystallite size as obtained from XRD. The DC resistivity for pure TiO2 nanoparticles is the highest while codoped samples exhibit low resistivity. The temperature dependent dielectric constant and dielectric loss possess step like enhancement and show the relaxation behavior. At room temperature, the dielectric function and dielectric loss decrease rapidly with increase in frequency and become almost constant at the higher frequencies. Such a decrease in dielectric loss is suitable for energy storage devices.